Dukungan IFRS pada FDI dalam Peningkatan Kemakmuran Negara - Riesanti Edie Wijaya (Jurusan Akuntansi Politeknik Negeri Malang, 2018)
Abstract The purpose of this study is to investigate the role of IFRS application in economic welfare. Based on macroeconomics data from World Bank, the regression analysis was used to observe the relationship between IFRS and FDI. The IFRS fail to entice FDI flow in Indonesia. Unfortunately, the financial reporting quality has not increased yet by IFRS application. Furthermore, IFRS fail to lessen the risk of doing business in Indonesia. FDI investments are not intended for transferring technology and knowledge. To sum up, FDI potentially become a burden for the economic welfare. Abstrak Tujuan dari penelitian ini adalah untuk menyelidiki peran aplikasi IFRS dalam kesejahteraan ekonomi. Berdasarkan data makroekonomi dari Bank Dunia, analisis regresi digunakan untuk mengamati hubungan antara IFRS dan FDI. IFRS gagal untuk memikat aliran FDI di Indonesia. Sayangnya, kualitas pelaporan keuangan belum meningkat dengan aplikasi IFRS. Selanjutnya, IFRS gagal mengurangi risiko berbisnis di Indonesia. Investasi FDI tidak dimaksudkan untuk mentransfer teknologi dan pengetahuan. Singkatnya, FDI berpotensi menjadi beban bagi kesejahteraan ekonomi.